Competencies of Digital Culture in Mathematics Education and their Formation - Oleg Kuzenkov; Irina Zakharova (Современные информационные технологии и IT-образование, 2021)
The article is devoted to the problem of the development of digital culture within the existing educational system based on the educational standards of FGOS3++. The current level of development of society requires the formation of new competencies that meet the needs of digitalization in all spheres of life. The assimilation of digital culture by a teacher, first of all, by a mathematics teacher, is of extremely high importance, since this is the key to the acquisition of digital competencies by students. The purpose of the article is to analyze the ways of updating educational programs of mathematical training and modernization experience on specific examples. Two ways of modernization are considered: expanding the list of formed competencies (adding additional competencies related to digital skills) or deepening the content of formed competencies through a system of indicators. Both methods involve updating the results of training both for each working discipline and for the entire educational program as a whole. An important aspect of modernization is the revision of the evaluation fund, taking into account the emergence of new electronic forms of control, which involve the application and development of the acquired knowledge in the field of information and «end-to-end» technologies. The actual direction of modernization of mathematical education is the development of research training and, in particular, the application of project approaches. As a result of the research, an example of the modernization of the educational program for bachelor's degree training in the direction 01.03.01 Mathematics to ensure the competencies of digital culture is given. The second considered example is based on the results of updating the discipline «Mathematical modeling of selection processes» for bachelors of the direction 01.03.02 Applied Mathematics and Computer Science.